Analysis of watersheds and river systems: short course - Simons, Daryl B., author; Li, Ruh-Ming, author; Ward, Timothy J., author; Shen, H. W., author; Ponce, V. Miguel, author; Eggert, Kenneth G., author; Chen, Yung-Hai, author; Simons, Robert K., author; Brown, Glenn O., author; Duong, Nguyen, author (Colorado State University. Libraries, 1979)
This short course is designed for individuals dealing with the analysis of watersheds and rivers. Practical applications concerning physical processes will be emphasized.
Chapter 1. General introduction / Daryl B. Simons and Ruh-Ming Li -- Chapter 2. Introduction to watershed and river analysis / Daryl B. Simons and Ruh-Ming Li -- Chapter 3. Physical processes governing response of watersheds and rivers / Daryl B. Simons, Timothy J. Ward and Ruh-Ming Li -- Chapter 4. Sediment transport / H. W. Shen -- Chapter 5. Alluvial bed roughness / H. W. Shen -- Chapter 6. Overview of flood routing methods / Ruh-Ming Li and V. Miguel Ponce -- Chapter 7. Water routing and yield from watersheds, Part I and II / Ruh-Ming Li, Daryl B. Simons, and Kenneth G. Eggert -- Chapter 8. Water routing in rivers / Yung-Hai Chen -- Chapter 9. Stage discharge relations / Robert K. Simons, Ruh-Ming Li, and Daryl B. Simons -- Chapter 10. Watershed sediment yield / Ruh-Ming Li, Daryl B. Simons, and Timothy J. Ward -- Chapter 11. Unsteady sediment routing models in rivers / Yung-Hai Chen and Daryl B. Simons -- Chapter 12. Known discharge sediment routing / Glenn O. Brown and Ruh-Ming Li -- Chapter 13. Landslide potential delineation / Timothy J. Ward, Ruh-Ming Li, and Daryl B. Simons -- Chapter 14. Application of Kalman filtering in watershed and river analysis / Nguyen Duong -- Chapter 15. Handheld calculator programs for analysis / Kenneth G. Eggert, Ruh-Ming Li, and Daryl B. Simons -- Chapter 16. Overview of case studies and data management / Daryl B. Simons, Ruh-Ming Li, and Nguyen Duong -- Chapter 17. Canal and channel design and river response analysis / Daryl B. Simons, Ruh-Ming Li, and Yung-Hai Chen -- Chapter 18. Degradation and aggradation analysis / Ruh-Ming Li and Daryl B. Simons -- Chapter 19. Watershed best management analysis / Ruh-Ming Li, Timothy J. Ward, and Daryl B. Simons -- Chapter 20. Large river basin analysis: Yazoo River Sedimentation Study / Daryl B. Simons and Ruh-Ming Li.
Short course: Analysis of Watersheds and River Systems, Session I and II, held on May 28-June 1, 1979 and June 4-June 8, 1979 at Colorado State University, Fort Collins, Colorado.
Speakers: Dr. E. V. Richardson, Dr. David Duttweiller, Mr. Lee Mulkey, Dr. Stanley A. Schumm, Dr. Daryl B. Simons, Dr. Ross Carder.
Keywords: Watershed management -- Analysis; Rivers -- Analysis; River sediments; Sediment transport